Використання методів реінженірінгу для вдосконалення процесу розрахунків за вантажні перевезення АТ «Укрзалізниця» - Кириченко, Ганна; Бердниченко, Юлія; Белінський, Дмитро (ТзОВ «Галицька видавнича спілка», 2021)
In the conditions of post-crisis functioning, the enterprises come up against the task of ensuring the sustainability of development, which is possible due to the formation of an effective mechanism for managing changes at the enterprise. The introduction of the reengineering of business processes as an innovative method of strategic change management is undoubtedly relevant in the conditions of the activity of domestic enterprises in unsteady market conditions.
Use of reengineering methods to improve the freight transportation payment process at JSC Ukrzaliznytsya
Keywords: 656.2